Using PlanetScope-derived time-series elevation models and orthophotos to track glacier 3D dynamics in mid-latitude mountain regions - Shengxi Gui; Rongjun Qin (GIScience & Remote Sensing)
Assessing glacier surface height changes provides crucial insights into glacier mass loss and the impact of climate variability. Remote sensing images play a vital role in providing data points for monitoring. Oftentimes, the glacier height change observation is sparse with notable time intervals, yet it is unclear whether these sparse observations are within seasonal variations. Thus, data with high-temporal resolution are necessary to 1) establish sufficiently dense observations to achieve enhanced conclusions; 2) derive higher-level data, such as motion velocity, to assess the level of global warming and climate change. PlanetScope satellite constellations can provide global daily/weekly observations with a 4 m ground sample distance (GSD). In this work, we report a study on monitoring fast dynamic glaciers in mid-latitude mountain regions in America and Asia using the derived time-series 3D elevation models from PlanetScope. The study includes three sites: La Perouse Glacier (North America), Viedma Glacier (South America), and Skamri Glacier (Central Asia). Based on PlanetScope data, we derived near bi-monthly 4-m resolution 3D elevation models for the year of 2019–2023 using satellite stereo photogrammetry, to track the ice flow in 3D. The results can be used to decorrelate the factors from seasonable variation: the Viedma Glacier is observed thinner over time with a slower flow rate; although through a single and short-term observation, the thinning rate of La Perouse Glacier is shown accelerating, we did not observe evidence that La Perouse Glacier and Skamri Glacier have obvious thinning other than its seasonable variations within a few years of time frames (since the PlanetScope images were available). By focusing on the local surface motion variations, our study shows that the glacier velocity varies with regional climate, geography, and hydrology, with a notable 45-day lag response between climate factors and flow speed in Viedma and Skamri Glaciers.